Ensaios em econometria aplicada - Souza, Rafael Martins de (2009)
This thesis has three chapters. Chapter 1 explores literature about exchange rate pass-through, approaching both empirical and theoretical issues. In Chapter 2, we formulate an estate space model for the estimation of the exchange rate pass-through of the Brazilian Real against the US Dollar, using monthly data from August 1999 to August 2008. The state space approach allows us to verify some empirical aspects presented by economic literature, such as coe cients inconstancy. The estimates o ffer evidence that the pass-through had variation over the observed sample. The state space approach is also used to test whether some of the 'determinants' of pass-through are related to the exchange rate pass-through variations observed. According to our estimates, the variance of the exchange rate pass-through, monetary policy and trade ow have infuence on the exchange rate pass-through. The third and last chapter proposes the construction of a coincident and leading indicator of economic activity in the United States of America. These indicators are built using a probit state space model to incorporate the deliberations of the NBER Dating Cycles Committee regarding the state of the economy in the construction of the indexes. The estimates o ffer evidence that the NBER Committee weighs the coincident series (employees in nonagricultural payrolls, industrial production, personal income less transferences and sales) di fferently way over time and between recessions. We also had evidence that the number of employees in nonagricultural payrolls is the most important coincident series used by the NBER to de fine the periods of recession in the United States.